2016
DOI: 10.1186/s40168-015-0145-y
|View full text |Cite
|
Sign up to set email alerts
|

Human milk microbiota profiles in relation to birthing method, gestation and infant gender

Abstract: BackgroundHuman milk is an important source of bacteria for the developing infant and has been shown to influence the bacterial composition of the neonate, which in turn can affect disease risk later in life. Very little is known about what factors shape the human milk microbiome. The goal of the present study was to examine the milk microbiota from a range of women who delivered vaginally or by caesarean (C) section, who gave birth to males or females, at term or preterm.MethodsMilk was collected from 39 Cauc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

34
284
10
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 345 publications
(336 citation statements)
references
References 42 publications
34
284
10
8
Order By: Relevance
“…Recent studies have suggested that milk bacterial communities originate from the maternal host or environmental sources including: (i) vaginal or skin bacteria (depending on the delivery model)1718; (ii) the infant’s oral and skin bacteria, which may contaminate milk during breastfeeding because of milk flow back into the mammary duct19; and (iii) bacteria in the maternal gastrointestinal tract, which translocate through the bacterial entero-mammary pathway into the mammary glands, and then to the milk20. However, Hunt et al 3.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have suggested that milk bacterial communities originate from the maternal host or environmental sources including: (i) vaginal or skin bacteria (depending on the delivery model)1718; (ii) the infant’s oral and skin bacteria, which may contaminate milk during breastfeeding because of milk flow back into the mammary duct19; and (iii) bacteria in the maternal gastrointestinal tract, which translocate through the bacterial entero-mammary pathway into the mammary glands, and then to the milk20. However, Hunt et al 3.…”
Section: Discussionmentioning
confidence: 99%
“…Their results and the findings of our current study provide further confirmation that the mode of feeding affects the oral microbiota of infants from the early neonatal period (4 weeks of age) and up to 3 months of age. Human breast milk also has its own unique microbiome29, so breast-feeding of infants may assist in the transmission of ‘healthy’ microflora from mothers to their infants. However, it is also known that pathogenic viruses (human immunodeficiency virus, Zika virus, cytomegalovirus) and bacteria ( Candida spp., Klebsiella spp., Acinetobacter spp.…”
Section: Discussionmentioning
confidence: 99%
“…59 Further research on the HM microbiota is needed to reveal how they interact with other components found in HM and how these constituents work together to facilitate healthy maturation of the infant GI microbiota. 69,70 Continued investigation of how the HM microbiota differs between mothers as well as the effects of transient exposure to certain bacteria, without colonization, will provide further insight into the complex and long-lasting functional differences witnessed between growing infants. 70 …”
Section: Human Milk Microbiotamentioning
confidence: 99%
“…69,70 Continued investigation of how the HM microbiota differs between mothers as well as the effects of transient exposure to certain bacteria, without colonization, will provide further insight into the complex and long-lasting functional differences witnessed between growing infants. 70 …”
Section: Human Milk Microbiotamentioning
confidence: 99%